Youth Unemployment and The Rentier Economy in Brunei: Lessons from Norway - Musa, S.F.P.; Basir, K.H. (Universiti Sains Islam Malaysia, 2024)
This study is a comparative analysis between two rentier economies namely Brunei and Norway. Brunei is an oil-rich country however currently experiencing growing youth unemployment; recorded at 28.4%, the highest value recorded by International Labour Organization (ILO) so far for Brunei over the years. This qualitative study uses focus groups to investigate the issue of youth unemployment and occupational aspirations. The thematic analysis conducted revealed that occupational aspirations of youths in Brunei are very much related to the economic conditions, more specifically the rentier economy. This gives rise to a ‘rentier mentality’ of youths in Brunei whereby there is a tendency for youths to aim towards prestigious occupations. Norway’s education and labour market policies can be seen as a role model for Brunei due to its similar rentier economy and more so for having one of the lowest youth unemployment level in the world i.e. 9.4% in 2017. This study found that the key lessons from Norway for Brunei lie in the diverse education system which not only focuses on the academics but places greater emphasis on vocational training and entrepreneurial skills. This results in youths that are ready for the labour market and a smooth transition from education to work.